2008
DOI: 10.1007/s12022-008-9038-y
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer, Thyroiditis and Dietary Iodine: A Review Based on the Salta, Argentina Model

Abstract: Factors that should be considered when studying the effect of dietary iodine in the development of thyroid cancer include pathological criteria, diagnostic techniques, screening programs, radioactive fallout, and standard of medical care in the studied population. In most surveys, papillary carcinoma forms the largest group of thyroid malignancies, both before and after iodine prophylaxis where an increase in the papillary:follicular carcinoma ratio is also noted. Undifferentiated carcinomas decrease after sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 89 publications
1
46
0
3
Order By: Relevance
“…Iodine intake is considered a risk factor for thyroid carcinogenesis, especially in iodine‐deficient countries 1, 2. Experimental studies revealed that the rate of occurrence of thyroid carcinoma was higher in animals fed a low iodine diet than in animals fed a control diet 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine intake is considered a risk factor for thyroid carcinogenesis, especially in iodine‐deficient countries 1, 2. Experimental studies revealed that the rate of occurrence of thyroid carcinoma was higher in animals fed a low iodine diet than in animals fed a control diet 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…The major objective in the evaluation of a nodule is the exclusion of malignancy. The risk of malignancy in a thyroid nodule varies between 5% and 10% in iodine-sufficient countries, and the amount of iodine supplemented in table salt can influence this incidence (3).…”
Section: Introductionmentioning
confidence: 99%
“…Increased radiation exposure in childhood due to the greater use of pediatric computed tomography scanning has been suggested as potentially relating to the increasing rates in the recent decades (3). Other factors potentially contributing to the temporal trends and geographic variations include obesity (16)(17)(18), iodine intake (10,19), environmental exposure to polychlorinated biphenyls and dioxins (20), use of fertility drugs (21) …”
mentioning
confidence: 99%